2002
DOI: 10.1002/mrm.10233
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intracellular pH, blood, and tissue oxygen tension on T relaxation in rat brain

Abstract: The effects of intracellular pH (pH i ), paramagnetic macroscopic, and microscopic susceptibility on T 1 in the rotating frame (T 1 ) were studied in rat brain. Intracellular acidosis was induced by hypercapnia and pH i , T 1 , T 2 , diffusion, and cerebral blood volume (CBV) were quantified. Taking into account the CBV contribution, a prolongation of parenchymal T 1 by 4.5% was ascribed to a change in tissue water relaxation caused by a one unit drop in pH i . Blood T 1 was found to prolong linearly with bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
110
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(120 citation statements)
references
References 46 publications
10
110
0
Order By: Relevance
“…The SL-EPI sequence has the advantage of rapid acquisition of T 1 data compared to a T 1 -prepared TSE sequence. This new sequence should allow studies that determine the dependence of T 1 on blood oxygenation levels in vitro (9) to be performed in vivo in a clinical setting. As an example, T 1 mapping could be used to detect ischemia in regions in the brain with some basic modifications, such as the use of an appropriate RF coil to SL flowing blood, for example, in the carotids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SL-EPI sequence has the advantage of rapid acquisition of T 1 data compared to a T 1 -prepared TSE sequence. This new sequence should allow studies that determine the dependence of T 1 on blood oxygenation levels in vitro (9) to be performed in vivo in a clinical setting. As an example, T 1 mapping could be used to detect ischemia in regions in the brain with some basic modifications, such as the use of an appropriate RF coil to SL flowing blood, for example, in the carotids.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, we are currently pursuing studies that compare results from T 2 , T 2 *, and T 1 -weighted fMRI experiments to elucidate mechanisms of Blood Oxygenation Level Dependent (BOLD) contrast as the relative contribution of susceptibility to the relaxation times will differ between sequences (9). Further, the magnetic susceptibility of blood affects the MR signal in brain parenchyma differently depending on the size of the vessel.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, T 1 -weighted MRI of H 2 17 O was recently used to measure cerebral and tumor perfusion (13,14). The sensitivity of T 1 to a variety of physiological parameters has also been demonstrated (15).…”
mentioning
confidence: 99%
“…In contrast, the physiological source of T1ρ is less well‐understood. Prior studies have shown that T1ρ is sensitive to changes in pH, with signal increasing with acidity (Heo et al., 2014; Kettunen et al., 2002). Because of this, fT1ρ signal may reflect increases in acidic metabolites such as H + , glutamate, and lactate in tissue following neuronal activation (Belanger et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This technique aims to quantitatively map the spin‐lock–based T1ρ relaxation time temporally and is sensitive to chemical exchange of protons between water and amide, hydroxyl, and/or amine groups (Jin, Autio, Obata, & Kim, 2011). This chemical exchange is influenced by pH and metabolite concentration (e.g., glucose and glutamate) (Jin et al., 2011; Kettunen, Gröhn, Silvennoinen, Penttonen, & Kauppinen, 2002), which have been shown to change in response to neural activation prior to changes in blood flow (Belanger, Allaman, & Magistretti, 2011). T1ρ relaxation is also sensitive to stimulus‐induced rotary saturation (SIRS), which may directly measure neuronal currents (Witzel, Lin, Rosen, & Wald, 2008).…”
Section: Introductionmentioning
confidence: 99%